THE FREQUENCY OF BENIGN PAROXYSMAL POSITIONAL VERTIGO IN CHRONIC MIGRAINE (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of benign paroxysmal positional vertigo (BPPV) in chronic migraine. Study design: Cross-sectional study Place and duration: Neurology Department of Pak Emirates Military Hospital, Rawalpindi, for a duration of 6 months i.e. from July/2024 till Dec/2024 Patients and methods: After obtaining written informed consent, 87 patients who met the selection criteria were enrolled. Frequency, intensity, duration, VAS pain score for migraine were recorded. All patients underwent the Dix-Hallpike technique that was used for the positioning exam and BPPV was documented if present. All findings were then subjected to statistical analysis. Results: The mean age of the patients was 40 ± 6.69 years. The median frequency of headache at baseline was 8 (2) per month. The median duration of headache at baseline was 10 (9). The median VAS score at baseline was 7 (2). There were 33 (37.9%) males and 54 (62.1%) females in the study. BPPV was present in 7 (8%) patients, out of which the left side was involved in 2 (2.3%) patients, right was involved in 2 (2.3%) patients and both sides were involved in 3 (3.4%) patients. Conclusion: In patients with chronic migraine, BPPV can be encountered and has a frequency of 8%.